Frontal sinus squamous cell carcinoma with intracranial, extraaxial extension in a dog with chronic sinonasal aspergillosis. Issue 1 (1st March 2021) - Strohmayer, Carina; Hirt, Reinhard A.; Gradner, Gabriele M.; Högler, Sandra; Kneissl, Sibylle
Abstract: A 10‐year‐old neutered male Golden Retriever with a history of chronic sinonasal aspergillosis was presented for unilateral nasal discharge, severe pain when opening the mouth, mildly reduced mentation and disorientation. CT revealed a mixed osteoproductive and osteolytic soft tissue mass that extended intracranially from the frontal sinus. Additionally, left‐sided nasal turbinate destruction was evident, consistent with chronic destructive rhinitis. The dog was euthanised, and the mass was diagnosed as frontal sinus squamous cell carcinoma (SCC) with intracranial‐extradural extension. This case report correlates diagnostic imaging and necroscopic findings of an osteoproductive and osteolytic frontal sinus SCC in a dog.